Maresin1 ameliorates sepsis-associated lung injury by inhibiting the activation of the JAK2/STAT3 and MAPK/ NF-κB signaling pathways. (November 2020) - Wang, Fuquan; Wang, Min; Wang, Jingxu; Chen, Ming; Sun, Shujun; Yao, Shanglong; Xia, Haifa
Abstract: Sepsis-associated acute lung injury (ALI) is a clinically critical disease that carries a high mortality rate. The pathogenesis of sepsis-associated ALI has not yet been precisely elucidated and there is a lack of effective treatment. As a new endogenous docosahexaenoic acid (DHA)-derived lipid mediators, Maresin1 has a significant dual role of anti-inflammatory and promoting inflammation regression. In this study, we established the sepsis model by the cecal ligation and puncture method (CLP) to explore the effect of Maresin1 on sepsis-induced lung injury. We found that the intervention of Maresin1 could significantly attenuate the sepsis-induced inflammatory responses, characterized by the down-regulation of the level of IL-1β, IL-6, TNF-α, MPO, etc. Maresin1 could also significantly decrease the number of neutrophils in lung tissue, thus improving the related lung injury indicators. Our experiment clarified that the protective effect of Maresin1 on sepsis-associated lung injury is closely related to its inhibition function of JAK2/STAT3 and MAPK/NF-κB signaling pathways. Our findings provide new research directions and therapeutic targets for sepsis-associated ALI. Highlights: Maresin1 could reduce the inflammatory cytokines level and decrease the neutrophil infiltration in sepsis-induced ALI. Maresin1 improves the sepsis-induced ALI via its inhibition of the JAK2/STAT3 signaling pathway. Maresin1 could inhibit the activation of MAPK/ NF-κB signaling pathway in sepsis-induced ALI.